'May I do something for you?': The effects of audio-visual material (captioned and non-captioned) on EFL pragmatic learning. (March 2022) - Barón, Júlia; Celaya, M. Luz
The present study deals with the effect of audio-visual material for second language (L2) pragmatic learning in the foreign language classroom. More specifically, it analyzes whether being exposed to captioned and non-captioned input in an experimental condition entailing no instruction on pragmatics might have any influence on the learners' pragmatic performance. To this aim, two intact classes ( N = 31) of learners of English as a foreign language (EFL) at a B1 level were exposed to videos with captions and without captions, respectively. Before and after watching the videos, all the students were asked to carry out a role-play task with situations like those in the videos. A mixed-methods approach was used to analyze the learners' performance in terms of types and number of strategies to perform speech acts (quantitative) and in terms of pragmatic appropriateness (qualitative). Findings show that both groups used more polite strategies after watching the videos, regardless of the captioned/non-captioned condition, which seems to confirm the contribution of audio-visual material for the learning of the L2 pragmatics in an incidental way. Concerning pragmatic appropriateness, we found that learners in the captioned condition produced more pragmalinguistically appropriate role-plays than learners in the non-captioned condition, thus suggesting a positive effect of captioned material on the learning of the L2 pragmatics. Such results are discussed in relation to the few previous similar studies in the field.